Improving the Methodology of Using a Stratified Approach in the Formation of Legal Competencies in Future Teachers (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
the article reflects the relevance and importance of using a differentiated approach in the formation of legal competence of future teachers, the model of improving legal competence, and its classification in pedagogical principles.